Role of Thrips Omnivory and Their Aggregation Pheromone on Multitrophic Interactions Between Sweet Pepper Plants, Aphids, and Hoverflies - Vaello, Teresa; Pineda, Ana; Marcos-García, Mª Ángeles (Frontiers in Ecology and Evolution, 2019)
In complex food webs, plants are commonly attacked by multiple herbivorous species, affecting the preference and performance of other herbivores and natural enemies. The role of omnivorous insects in ecosystems may be more complex because of the consumption of both plant and animal organisms. However, the effect on herbivores and their natural enemies through non-prey omnivorous insects, has received little attention so far. The main goal of this study was to investigate whether the dual herbivore interaction between aphids and thrips (which can act as an omnivore), on a sweet pepper system, may affect different trophic levels, from plant and aphid performance until the third trophic level, i.e. preference and performance of the predatory hoverfly Sphaerophoria rueppellii. Additionally, we tested whether the aggregation pheromone from the thrips Frankliniella occidentalis, could disturb the oviposition behaviour of the predatory hoverfly. Our results show how the presence of thrips decreases host plant and aphid performance. Furthermore, despite not affecting syrphid larval performance, thrips presence reduces fecundity of the adults that emerged from those larvae. Additionally, we observed that syrphids avoid ovipositing on plants containing either thrips or thrips aggregation pheromone. The present study reveals how the presence of a non-prey species pest or a non-prey semiochemical compound, can impact the behaviour and performance of a predator.